THE ROLE OF GREEN ENTREPRENEURIAL SKILLS IN ENHANCING PRODUCTION ECONOMY IN NIGERIA - Anabaraonye, Benjamin; Onnoghen , Usang.N.; Nwafor , Gideon.U.; Obinna , Chukwuemeka.J.K. (Covenant Journal of Entrepreneurship, 2024)
The national hunger, poverty, and unemployment challenges have motivated individuals and groups to float their business enterprises to achieve better living conditions. There is a clarion call to move the nation from an economy of consumption to production, enhancing Nigeria's good health and well-being through entrepreneurship education. Through literature review, participant observation, and data collection from relevant agencies, this study identified the role of green entrepreneurial skills in enhancing the production economy in Nigeria. It identified that green entrepreneurial skills will help achieve the United Nations Sustainable Development Goals (SDGs) 1,2, 4, and 13. This study defined the concept of entrepreneurship and green entrepreneurship. It further highlighted that entrepreneurial skills aim primarily to produce competent, skillful, and dynamic entrepreneurs who will effectively compete in the world of work. It also identified green entrepreneurial skills as necessary amidst the global challenges of climate change, thereby enhancing the production economy. The implementation of the findings of the study would help strengthen entrepreneurship and enhance the production economy in Nigeria. It concluded with the benefits of green entrepreneurship and a clarion call for further research on the role of green entrepreneurial skills in enhancing the production economy in Nigeria.